1997
DOI: 10.1007/s004410050788
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical differentiation of rat enteric neurons during pre- and postnatal life

Abstract: The presence of nitric oxide synthase (the enzyme which synthesizes nitric oxide), vasoactive intestinal peptide (VIP) and pituitary adenylyl-cyclase-activating peptide (PACAP) in the rat enteric nervous system between term (E18) and 90 days postpartum (P90) was investigated by immunohistochemistry. Neuronal maturity was ascertained by emanining for the presence of two novel neuron intermediate filament proteins: alpha-internexin, which is transiently expressed in developing neurons, and peripherin, which is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
10

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 50 publications
(69 reference statements)
3
32
1
10
Order By: Relevance
“…This development of the ENS is also associated with a time-dependent differentiation of specific neurochemically identified neuronal populations that has been described mainly in the prenatal period of mice (28). In rats, 5-HT expression appears early during the embryonic life whereas other mediators appear later such as nitric oxide (NO) by E18, VIP during the suckling period, and PACAP-27 during the weaning period (13). A recent study has also shown an increase in the vesicular acetylcholine transporter (VAChT) immunoreactivity in the mouse pup, which was correlated with the development of colonic migrating motor complexes (CMMCs) (19).…”
mentioning
confidence: 99%
“…This development of the ENS is also associated with a time-dependent differentiation of specific neurochemically identified neuronal populations that has been described mainly in the prenatal period of mice (28). In rats, 5-HT expression appears early during the embryonic life whereas other mediators appear later such as nitric oxide (NO) by E18, VIP during the suckling period, and PACAP-27 during the weaning period (13). A recent study has also shown an increase in the vesicular acetylcholine transporter (VAChT) immunoreactivity in the mouse pup, which was correlated with the development of colonic migrating motor complexes (CMMCs) (19).…”
mentioning
confidence: 99%
“…Our results are even more striking but still in line with these fi ndings, indicating that about three fourths (64-82%) of the myenteric neurons in the esophagus of adult rats were NADPH-d positive [9] . This proportion is much higher than those found in the other parts of the rat GI tract, where myenteric nitrergic neurons were found at lower proportions: 29-38% in the stomach [22] , 28% in the duodenum, 15-27% in the ileum [23,24] and 12-57% in the colon [25] . High proportions of esophageal myenteric nitrergic neurons have also been demonstrated in other species, such as cats (48-60%), opossums (35-51%) [7,26] , pigs (63%) [2,11] , monkeys (45%) [18] and even humans (55%) [27] .…”
Section: Introductionmentioning
confidence: 68%
“…Several clinical and experimental observations suggest that homeostatic control of gut function in a changing environment might be achieved through adaptive changes occurring in the enteric ganglia [34]. Recent studies in infants and children [35] indicate that the density of ganglion cells in the myenteric plexus decreases significantly with age during the first 3-4 years of life and that the neurochemical differentiation in rat is accomplished during the first month of postnatal live [17]. In rat also the total number of enteric neurons decreases significantly after birth [29].…”
Section: Discussionmentioning
confidence: 97%